Cantaloupe -A Food safety concern: Mini-Review - Hansel A Mina; Amanda J Deering (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Historically, the United States has positioned itself as one of the leading producers and consumers of melons in the world with a 2020 production value of over $295 million (excluding watermelons). It has been estimated that on average the per capita consumption of melons in the U.S. is about 24 pounds each year [1].